Village Tourism-Based Local Economic Development: An Approach to the Raled Model - Reta Giyanti Supratman; Muhammad Hasyim Ibnu Abbas (EcceS (Economics, Social, and Development Studies), 2022)
Selorejo Village, Malang Regency has tourism potential which is known as the Bumi Perkemahan Bedengan Tourism. However, Bumi Perkemahan Bedengan Tourism still needs to be developed optimally because this tourism has the potential to become sustainable tourism. The novelty of this research is to complement quantitative research methodologies related to the theme of developing village tourism potential, where there are research limitations from several previous studies, which are dominated by descriptive qualitative methods. The concept of Local Economic Development (LED) is deemed capable of optimizing available local resources by involving several stakeholders such as the Government, Local Communities, Business Actors, and Local Community Organizations. This research discusses tourism-based Local Economic Development (LED) that aims to examine the condition of Local Economic Development (LED) and provide insight in making plans or strategies for sustainable Local Economic Development (LED) in Bumi Perkemahan Bedengan Tourism. This article applies a quantitative approach with data analysis of RALED (Rapid Assessment Technique for Local Economic Development). Assessment of local economic development in Bumi Perkemahan Bedengan Tourism using the hexagonal concept of LED which consists of six aspects, namely target group, location factors, policy focus and synergy, sustainable development, governance, and management process. The results showed that the five aspects had met the good category. However, there is one aspect, namely the Target Group has a low index value of 45.92 which means that the condition of Local Economic Development in the aspect of the Target Group at the Bumi Perkemahan Bedengan is in a bad condition. Therefore, the target group aspect and the other two lowest aspects namely management process and location factors need attention for more improved in the efforts of Local Economic Development (LED) in the Bumi Perkemahan Bedengan Tourism.